Metabolic and Toxic Myelopathies - Kumar, Neeraj (Seminars in Neurology, 2012)
The myelopathies discussed in this article have an underlying metabolic or toxic etiology. They have many clinical, electrophysiologic, and neuropathologic similarities. Preferential involvement of the dorsal columns and/or corticospinal tracts is commonly seen. Variable degrees of peripheral nerve and/or optic nerve involvement may be present. In the presence of clinical or electrophysiologic evidence of peripheral nerve involvement, the term myeloneuropathy is commonly used.The metabolic and toxic myelopathies discussed here are divided into three categories: disorders due to an identified nutrient deficiency such as the subacute combined degeneration of cobalamin/vitamin B12 or copper deficiency, disorders that have a geographical predilection and are due to a suspected toxin such as lathyrism, and disorders due to a possible toxin but without a geographical predilection such as hepatic myelopathy (Table 1).
Keywords: myelopathy; metabolic; toxic